2014
DOI: 10.1186/1471-2458-14-1220
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of prior HIV testing among men who have sex with men in Cameroon: a cross-sectional analysis

Abstract: BackgroundRegular HIV testing is vital for timely linkage to the HIV care continuum and ensuring the success of behavioral and biomedical interventions to prevent HIV acquisition. Men who have sex with men (MSM) are a key population for HIV prevention, treatment, and care efforts globally. This study measures the factors associated with prior HIV testing among MSM in Cameroon.MethodsIn 2011, 272 and 239 MSM aged ≥ 18 were recruited from Douala and Yaoundé respectively using respondent-driven sampling (RDS) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
(73 reference statements)
2
12
0
3
Order By: Relevance
“…We found that having good HIV‐related knowledge and particularly, having access to and use of health‐related services was strongly associated with prior HIV testing among YMSM in Myanmar. This finding corroborates with earlier evidence, from studies conducted in other LMICs, that MSM who have access to HIV education and service programmes were more likely to have tested for HIV in a lifetime and in the past 6 months , and that having good knowledge on HIV transmission, prevention and treatment was positively associated with HIV testing practice . However, this should be interpreted with care given that the direction of this association is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…We found that having good HIV‐related knowledge and particularly, having access to and use of health‐related services was strongly associated with prior HIV testing among YMSM in Myanmar. This finding corroborates with earlier evidence, from studies conducted in other LMICs, that MSM who have access to HIV education and service programmes were more likely to have tested for HIV in a lifetime and in the past 6 months , and that having good knowledge on HIV transmission, prevention and treatment was positively associated with HIV testing practice . However, this should be interpreted with care given that the direction of this association is unknown.…”
Section: Discussionsupporting
confidence: 90%
“…14 Pada karakteristik klinis klien LSL, persentase tertinggi adalah tidak pernah mengalami gejala IMS sebesar 72,3%, hal ini sesuai dengan penelitian di Cameroon dalam kategori yang sama sebesar 71,29%. 15 IMS menjadi salah satu hal penting dalam penularan HIV, dari penelitian ini didapatkan keluhan-keluhan terkait dengan IMS. Berikut adalah 3 keluhan dengan persentase tertinggi yaitu rasa sakit/panas saat buang air kecil disertai nanah sebanyak 38 orang, perlukaan dan borok di kemaluan sebanyak 30 orang, serta jengger ayam di anus/ kemaluan sebanyak 22 orang.…”
Section: Metodeunclassified
“…Regular HIV testing, particularly in key populations with high HIV prevalence, plays a very important role in reducing new HIV infections through early HIV detection, and it is the first step in engaging infected people in the care and treatment cascade [ 24 ]. Early detection not only reduces the chance of HIV transmission but also enables timely treatment to reduce HIV-related mortality and morbidity [ 28 ].…”
Section: Introductionmentioning
confidence: 99%